1995
DOI: 10.1209/0295-5075/32/9/011
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Susceptibility in U 0.9 Th 0.1 Be 13 : Evidence of a Transition from a Paramagnetic to a Quadrupolar Kondo Ground State

Abstract: We test the quadrupolar Kondo scenario in U0.9Th0.1Be13 by measurements of the non-linear susceptibility. We found our non-linear-susceptibility data to be consistent with a transition below T ∼ 6K from a magnetic (f3) to a quadrupolar (f2) doublet ground state of the U atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…In every case, the characteristic energy scale is too large for all of these mixed-valent runs to account for the experimental data. We conclude that the scenario of Aliev et al [6], suggesting that UBe 13 is more strongly mixed valent than anticipated previously, and that doping with Th increases the 5f 2 weight (driving the system closer to the quadrupolar Kondo limit), is qualitatively consistent with our results.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In every case, the characteristic energy scale is too large for all of these mixed-valent runs to account for the experimental data. We conclude that the scenario of Aliev et al [6], suggesting that UBe 13 is more strongly mixed valent than anticipated previously, and that doping with Th increases the 5f 2 weight (driving the system closer to the quadrupolar Kondo limit), is qualitatively consistent with our results.…”
supporting
confidence: 93%
“…While the nonlinear magnetic susceptibility [5] is suggestive of a magnetic trivalent state, the rather weak temperature dependence of the linear susceptibility is more consistent with a nonmagnetic tetravalent state. Recently, following experiments on the nonlinear susceptibility of U 0.9 Th 0.1 Be 13 , Aliev et al [6] suggested a different physical regime, in which strong quantum fluctuations drive the uranium ions to a mixed-valent state.Here we explore the possibility of a mixed-valent state in the framework of the two-channel Anderson model [3], which consists of Γ 8 conduction electrons carrying both spin (σ =↑, ↓) and quadrupolar (α = ±) quantum labels, hybridizing via a matrix element V with a local uranium ion. The latter is modeled by a Γ 3 quadrupolar doublet in the 5f 2 configuration and a Γ 6 magnetic doublet in the 5f 3 configuration, separated in energy by ǫ f = E(5f 2 ) − E(5f 3 ).…”
mentioning
confidence: 99%
“…configuration degeneracy with is lifted with Th substitution [28]. We refer the necessary intermediate valance calculation to a future work.…”
Section: +mentioning
confidence: 99%
“…The negative value of χ 3 was previously found in some non-Fermi liquid alloys, e.g., in Na x CoO 2 , which is believed to be close to a ferromagnetic quantum critical point [17]. In the case of UBe 13 [18], U 0:9 Th 0:1 Be 13 [19], and UCu 5 À x Pd x [20], the presence of nonlinear susceptibility was taken as an evidence for an electric quadrupole Kondo effect. However, the power-law dependence of the susceptibility presented above for x¼0.32 does not support a quadrupolar Kondo effect scenario, for which the susceptibility is expected to behave like χðTÞp ffiffiffi T p [21].…”
Section: Magnetic Susceptibility and Magnetizationmentioning
confidence: 73%